Effect of undifferentiated connective tissue dysplasia on the development of vesicoureteral reflux in infants - Petritsa, N. A.; Lukyanenko, N. S.; Kens, K. A.; Tretyak, B. I. (Journal of Education, Health and Sport, 2017)
Introduction. Taking into consideration annual increase in the number of patients, the problem of congenital malformations of urinary organs, especially in infants diagnosed with vesicoureteral reflux, is becoming increasingly relevant. One of the main underlying causes of congenital malformations is the microanomalies of the internal organs, which can develop and enlarge depending on the peculiarities of connective tissue structure so they are regarded as undifferentiated connective tissue dysplasia. Polymorphism or mutations of a large number of genes in different combinations play the role in the occurrence of this pathology, as well as the effect of various environmental factors. The objective of the study was to establish the possible associations between the peculiarities of the distribution of polymorphic variants of GSTM1 and GSTT1 genes and rs565470 of a type IV collagen COL4A1 gene polymorphism with undifferentiated connective tissue dysplasia and vesicoureteral reflux in children. Materials and methods. We examined 49 children with II-IV stage vesicoureteral reflux, 15 children with pyelonephritis and 42 children who were systemically well. Oxiprolin was detected in the urine and the determination of the genotypes/alleles of the polymorphic locus rs565470 of COL4A1 gene was carried out, as well as the presence of the deletion alleles of GSTM1 0/0 and GSTT1 0/0 genes in the genotype of the child by Restriction Fragment Length Polymorphism method from the blood. Discussion. The carrier rate of GSTM1 0/0 zero-allele in the genotype was determined in 51.4% of the examined children, which is associated with its predisposition to the inflammatory process of the kidneys. The carriage of the combination of GSTT1 0/0 + GSTM1 0/0 zero alleles was found in 22.6% of children and it is associated with the presence of undifferentiated connective tissue dysplasia and the tendency to vesicoureteral reflux. Following the genotyping of rs565470 of COL4A1 gene polymorphism in children with vesicoureteral reflux, compared with healthy controls, it was found that the CT genotype with the given polymorphism increases the risk of vesicoureteral reflux in infants by a factor of three (OR = 3.00, CI 95%: 1.08–8.37), and in the presence of this genotype in a child, the risk of developing undifferentiated connective tissue dysplasia, as well as vesicoureteral reflux, increases sevenfold (OR = 6.75; CI 95%: 1.40–32.55). Conclusions The obtained results allow assuming the association of rs565470 of COL4A1 gene polymorphism with the formation of undifferentiated connective tissue dysplasia and the development of vesicoureteral reflux in infants.